ANALISA KEBUTUHAN PENGEMBANGAN JARINGANJALAN DI KOTA PALEMBANG - Arliansyah, Joni; Taruna, Adi; Rhaptyalyani, Rhaptyalyani; Kurnia, Aztri Yuli (FSTPT Indonesia, 2015)
The economic growth and rapid population in Palembang City and the surrounding regions lead to the increased mobility of people and goods. Palembang City which is divided into two upstream and downstream areas by Musi River and they are currently connected only by one bridge namely Ampera Bridge. This results in traffic concentration on the main city streets and congestion takes place almost throughout the day and evenly throughout the City area.This study analyzes and discusses the condition of network services in Palembang City with or without the development of road network in the City, in which the Spatial Planning and Area of Palembang City up to 2037 plans to construct six bridges and the city ring road. This study only discusses the conditions of service of the road network in the next five years, that is up to 2019.The road network condition in Palembang City was simulated using a Palembang City transportation model developed with JICA STRADA program (System for Traffic Demand Analysis), where the ratio between traffic volume survey results with the results of the modeling for the year 2014 has a determination coefficient (R2) of 0.839. The results indicate that the development of Musi Bridge IV in 2017 and the Musi Bridge VI in 2019 is a solution to deploy traffic movement and reduce congestion significantly in Palembang City. If the construction of the two bridges is delayed, Palembang will then suffer from severe traffic congestion in both 2017 and 2019.